2021
DOI: 10.1039/d1ta05237c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient N2 reduction with the VS2 electrocatalyst: identifying the active sites and unraveling the reaction pathway

Abstract: Electrochemical nitrogen reduction reaction (NRR) is an effective method for sustainable production of NH3. However, a robust NRR electrocatalyst is predominantly required in order to active the inert N2 molecule....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Specifically, our previous work has verified that vanadium sulfide (VS x ) based materials, thanks to their promising metallic properties, are potential candidates for the ENRR catalyst. 28 To further figure out the relationship between the valence state of V and the ENRR activity of VS x , we herein designed and synthesized VS 2− x with hybrid valences (V 2+ and V 4+ ) and VS 2 (with pure V 4+ ) by controlling the V sources during the hydrothermal process. We found that the as-prepared VS 2 sample exhibited a prominent FE of 35.52% and a high ammonia yield of 41.21 μg mg cat −1 h −1 at a lower overpotential (−0.3 V vs. RHE).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, our previous work has verified that vanadium sulfide (VS x ) based materials, thanks to their promising metallic properties, are potential candidates for the ENRR catalyst. 28 To further figure out the relationship between the valence state of V and the ENRR activity of VS x , we herein designed and synthesized VS 2− x with hybrid valences (V 2+ and V 4+ ) and VS 2 (with pure V 4+ ) by controlling the V sources during the hydrothermal process. We found that the as-prepared VS 2 sample exhibited a prominent FE of 35.52% and a high ammonia yield of 41.21 μg mg cat −1 h −1 at a lower overpotential (−0.3 V vs. RHE).…”
Section: Introductionmentioning
confidence: 99%
“…Then, Yan and coworkers demonstrated the activity of VS 2 for the NRR through an experiment, where flower-like VS 2 was prepared and a high NH 3 yield of 34.62 μg h −1 mg cat −1 was achieved in 0.1 M HCl at −0.7 V, with a FE of 2.09% (Table 1). 66 In addition, V sites were demonstrated to be the active centers for the NRR using tannic acid and SCN − to complex the metal center. Therefore, the exposure of metal sites is very important for improving the NRR performance of VS 2 .…”
Section: Metal Sulfides For the Nrrmentioning
confidence: 99%
“…Nanomaterials with unique crystal structures, morphologies and chemical compositions are widely used in electrochemistry . Vanadium-based nanomaterials, in particular, exhibit excellent electrochemical properties. , Vanadium enables multiple electron transfers during electrochemistry due to its various valences. , There are several types of vanadium-based nanomaterials, including vanadium oxides, , vanadium sulfides, vanadium nitrides, , vanadates, , etc. These materials possess various structures, and they are used in a variety of electrochemical energy conversion applications .…”
Section: Introductionmentioning
confidence: 99%
“…In a VS 2 monolayer, there is a 2D electron–electron correlation between V atoms . Recently, Zhao et al synthesized flower-like VS 2 (FL-VS 2 ) as an electrocatalyst for NRR using a one-step hydrothermal method . FL-VS 2 shows a maximum NH 3 yield of 34.62 μg h –1 mg cat –1 and a Faraday efficiency of 2.09%, which is higher than those of comparable products.…”
Section: Introductionmentioning
confidence: 99%